Learning and Evolutionary Constraints on Linguistic Variability - Chiera, Alessandra; Adornetti, Ines; Ferretti, Francesco (Status Quaestionis, 2020)
In this paper, we offer some insights that might contribute to the debate about English as a lingua franca (ELF) by addressing some aspects related to the broader topic of language acquisition and evolution. Specifically, it is our claim that some features related to the emergence of ELF can be explained in reference to the ‘bottleneck of communication’ generated by the sensory and memory processing constraints involved in language production and comprehension. We will refer to the usage-based perspectives to language (e.g. Tomasello 2003) according to which the bottleneck provides a constraint that affects the language system, both at the processing and acquisition level, leading to predictive and rapid learning processes that, in turn, cause an item-based language change: those linguistic forms that are easier to learn and more efficient from a communicative point of view will tend to spread and supplant those that are not functional to communication. On an evolutionary timescale, a similar adaptation process can shape the languages in accordance with a tendency to simplification and uniformity. Such a tendency might be responsible for the emergence of a global language that serves communicative purpose. In the light of these considerations, a systematic use of ELF can be explained within an integrated framework that focuses on the contribution of more general processes of language acquisition, change and evolution.